The imbalance between regulatory memory B cells reveals possible pathogenesis involvement in pediatric immune thrombocytopenia. Issue 1 (1st January 2019) - Fang, Junyue; Lin, Li; Lin, Dijin; Zhang, Ruihao; Liu, Xiuli; Wang, Di; Duan, Chaohui; Lin, Xianghua
ABSTRACT: Introduction: CD19 + CD24 hi CD38 hi regulatory B cells (Bregs ) and CD19 + CD27 + memory B cells (Bmems ) are B cell subsets with specific immunoregulatory properties. In this study, the balance of these subsets was investigated in pediatric immune thrombocytopenia (ITP) patients, and the frequencies of Bregs and Bmems before and after first-line therapy were measured. Methods: Forty-nine pediatric ITP patients and 19 normal controls were enrolled in this study. The total CD19 + B cells, Bregs and Bmems in the peripheral blood (PB) of all cases were measured by flow cytometry. Results: We found higher frequencies of total CD19 + B cells and Bmems in newly diagnosed ITP patients than those in normal controls ( p < 0.01), whereas the frequencies of CD19 + CD24 hi CD38 hi Bregs was significantly lower in ITP patients ( p < 0.001). After therapy with MP + IVIG, the level of CD19 + CD24 hi CD38 hi Bregs and Bmems were almost normalized. Conclusion: Our results indicated that pediatric ITP patients were characterized by a decline in CD19 + CD24 hi CD38 hi Bregs and increment of CD19 + CD27 + Bmems, and an increase of total CD19 + B cells in their peripheral blood.